Highlighting the Potential Role of Exosomes as the Targeted Nanotherapeutic Carrier in Metastatic Breast Cancer - Khera, Alisha; Alajangi, Hema K.; Khajuria, Akhil; Barnwal, Ravi P.; Kumar, Santosh; Singh, Gurpal (Current Drug Delivery, 2023)
Breast cancer, being the second most common type of cancer, is a leading cause of death in the female population. Of all the available treatments existing for breast cancer, exosomes appear as an important medium for the site targeted delivery of the drugs. Exosomes, unlike all the other extracellular vesicles, play a vital role in the transport of numerous biomolecules throughout the body and can easily be detected because of the presence of specific biomarkers. Apart from playing a wide variety of roles in the progression of many diseases, they are also responsible for tumor progression and metastasis in breast cancer. Exosomes and related engineering strategies are being discussed as nano-carrier for the delivery of different drugs in the case of breast cancer. Overall, we have discussed in this review the role of exosomes in breast cancer and the engineering strategies being devised for making them an efficient drug delivery system.
Keywords: engineering strategies